Viability and Survival of Lactobacillus casei Encapsulated with Whey, Sucrose and Maltodextrin Using Freeze-Dried Technique - Seveline; Tamara, Thasya (Universitas Djuanda, 2024)
Lactobacillus casei bacterium in probiotic products and in the human digestive tract could be decreased so that encapsulation preserved techniques need to protect the viability of Lactobacillus casei. The aimed of this study was to determine the ability and survival of L.casei with cryoprotectant materials that consist of a combination of whey with sucrose and whey with maltodextrin using freeze drying technique. The study design used was a complete randomized design consisting of five treatments with two replications which were control; whey 10% with sucrose 10%; whey 10% with maltodextrin 10%; whey 20% with sucrose 10%; and whey 20% with maltodextrin 10%. The anova test α = 0.05 was conducted, if significantly different than continued with a Duncan test. The results showed Lactobacillus casei encapsulated with whey 20% (v/v) and sucrose 10% (w/v) had the highest viability to the freeze drying process and during 28 days of storage at low temperatures (4°C) with the viability of each amounted to 92.66% and 90.38%. Lactobacillus casei with whey 20% (v/v) and maltodextrin 10% (w/v) was the best survival to 0.5% bile salts and low pH (pH 2). The best result was Lactobacillus casei with whey 20% (v/v) and maltodextrin 10% (w/v) to encapsulated and protected the bacterium.